Monday, 20 April 2015

SBI PO Quantitative Aptitude Quiz -4

Direction (Q. 1 - 2): What will come in place of question mark (?) in the following number series?

1. 12, 30, 56, 90, 132, ?

1) 178 2) 182 3) 185 4) 189 5) 196

2. 91, 381, 871, 1561, 2451, ?

1) 3541 2) 3621 3) 3681 4) 3716 5) 3772

3. 110, 440, 990, 1760, 2750, ?

1) 3680 2) 3610 3) 37820 4) 3840 5) 3960

4. 5, 6, 11, 20, 33, 50, ?

1) 64 2) 71 3) 78 4) 81 5) 84

5. 2, 7, 24, 77, 238, 723, ?

1) 1948 2) 1984 2) 2010 3) 2096 4) 2180

Direction (Q. 6 - 10): In each of these questions, two equations numbered I and II are given. You have to solve both the equations and find out the values of x and y and given answer.

1) If x > y

2) if x > y

3) if x < y

4) if x < y

5) if x = y or if there is no relation between x and y.

6. I. 4x2 – x – 5 = 0

II. 6y2 – 13y + 6 = 0

7. I. 7x + 13y = 9

II. 3x – 4y = 23

8. I. x = clip_image002

II. y = clip_image004

9. I. x2 + 14x + 49 = 0

II. 6y2 + 61y + 153 = 0

10. I. x2 + 11x + 30 = 0

II. 2y2 + y – 1 = 0

Answers

1. 2; 3 + 32, 5 + 52, 7 + 72

2. 1; 92 + 10, (19)2 + 20, (29)2 + 30

3. 5; 100 x 1.1, 200 x 2.2, 300 x 3.3, 400 x 4.4

4. 2; +12 – 02, +32 – 22, +52 + 42, +72 - 62

5. 5; x 3 + 1, x3 + 3, x 3 + 5, x 3 + 7 ……..

6. 5; I. 4x2 – x – 5

4x2 + 4x – 5x – 5 = 0

4x(x + 1) – 5 (x + 1) = 0

(4x - 5) (x + 1) = 0

X = -1, clip_image002[4]

II. 6y2 – 9y – 4y + 6 = 0

3y(2y - 3) – 2 (2y - 3) = 0

(2y - 3) (3y - 2) = 0

y = clip_image004[4], clip_image006

ie no relation exists between x and y.

7. 1; Multiplying eqn I by 3 and eqn II by 7 and adding both the equations:

clip_image008

∴ y = -2 and x = 5 ∴ x > y

8. 1; I. x = clip_image010 ∴ x = 43

II. y = clip_image012 ∴ y = + 27 ∴ x > y

9. 3; I. x2 + 14x + 49 = 0

(x + 7)2 = 0

X + 7 = 0 ∴ x = -7

II. 6y2 + 61y + 153 = 0

6y2 + 27y + 34y + 153 = 0

3y(2y + 9) + 17(2y + 9) = 0

(3y + 17) (2y + 9) = 0

Y = clip_image014, clip_image016 = -5.66, - 4.5

10. 3; I. x2 + 6x + 5x + 30 = 0

X(x + 6)+ 5(x + 6) = 0

(x + 5) (x + 6) = 0

X = -5, -6

II. 2y2 + 2y – y – 1 = 0

2y(y + 1) – 1 (y + 1) = 0

(2y - 1) (y + 1) = 0

Y = clip_image018, -1

∴ x < y

Advertisements

No comments:

Post a comment